Could mandatory vaccinations increase uptake in children?. (2nd November 2019) - Sisson, Helen
Abstract : Since the UK lost its measles-free status, mandatory vaccination for children has been considered as a method to increase uptake. Helen Sisson discusses the pros and cons of this approach